REPRESENTASI MORALITAS YANG BIAS GENDER PADA TRADISI PERKAWINAN MASYARAKAT GORONTALO DALAM NOVEL PERAWAN KEDUA KARYA LIZHA NURKAMIDEN - Nur Aina Ahmad (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
This research aims to describe the components of Gorontalo community’s customs or marriage tradition in the novel literary work Perawan Kedua by Lizha Nur Kamiden which contains elements of gender-biased morality. This research is a qualitative descriptive by using a sociology of literature approach. The data in this research were all forms of words, phrases, and sentences that represented moral values ​​or contain elements of morality that were gender biased in the marriage tradition of Gorontalo community. The main data source of this research was the novel Perawan Kedua by Lizha Nur Kamiden. Technique of collecting data used reading, listening, recording. Technique of analyzing data used sociology of literature studies. The results found that the representation of morality in the category of gender bias in marriage tradition of Gorontalo community in Perawan Kedua novel was found in bridal clothing, the stages of marriage, namely the tolobalango tradition (marriage proposal) as well as moodutu (traditional wedding delivery procession), and the kain putih pengantin (virgin white clothing).